Nutrient niche specificity for glycosaminoglycans is reflected in polysaccharide utilization locus architecture of gut Bacteroides species - Overbeeke, Annelieke; Hausmann, Bela; Nikolov, Georgi; Pereira, Fatima C.; Herbold, Craig W.; Berry, David (Frontiers in Microbiology, 2022)
Glycosaminoglycans (GAGs) present in the mucosal layer can be used as nutrients by certain intestinal bacteria, particularly members of the Bacteroides. GAG abundances are altered in some diseases such as inflammatory bowel diseases, which may affect microbial composition and activity, and it is therefore important to understand GAG utilization by members of the gut microbiota. Using growth assays, transcriptomics, and comparative genomics, we found that not all Bacteroides species able to degrade chondroitin sulfate (CS) could also degrade hyaluronan (HA), despite having lyases which act on both compounds. We propose that in the model organism Bacteroides thetaiotaomicron, the gene BT_3328 may be essential in HA breakdown. Furthermore, degradation of both compounds provides public goods for other Bacteroides, including non-degraders, suggesting that cooperative degradation as well as cross-feeding may be widespread in the mucosal glycan utilization clade.